(untitled) (Revista de Ciências Agroveterinárias, 2010)
The competition in the market has stimulated the winery industry to improve the management of vineyards and, consequently, the quality of grapes. Among these practices is the cluster thinning. However, there are no criteria to indicate the appropriate level of cluster thinning. To determine the effect of this practice, an experiment was conducted in Bento Gonçalves, RS, during the growing seasons of 2004/2005, 2005/2006, and 2006/2007, with 8-10 years old ‘Cabernet Sauvignon’ grapevines, grafted on Paulsen 1103 rootstock, planted at a spacing of 1.5 x 3 m, conducted in the horizontal overhead trellis and submitted to mixed pruning method (spur and cane). The cluster thinning was made at the beginning of maturity (50% of fruit color change), and the criteria to define the number of cluster thinning levels studied at different growing seasons were the maximum available number of bud burst and clusters/plant. Therefore, clusters were thinned by leaving: 5, 10, 20, and 30 clusters/ plant in 2004/2005; 15, 25, 40, 60, and 80 clusters/ plant in 2005/2006; and 15, 25, 40, and 60 clusters/ plant in 2006/2007. The trial followed a completely randomized block design, with five replicates of six plants (experimental unit). The data were analyzed by orthogonal polynomial contrasts. The effects of cluster thinning were more intense in the first year (2004/ 2005), when a water restriction occurred. In this year, the reduction in the number of clusters per plant significantly increased the fresh mass of berries and clusters, and increased the pH and °Brix of the juice. With the reduction of up to 83.3% in the number of clusters/plant (reduction from 30 to 5 clusters/plant), there was an increase of only 3.4% in the values of °Brix. In the following year (2005/2006), there was no effect of cluster thinning on grapes’ physicochemical attributes. In the third year (2006/2007) there was an increase of oBrix only for the treatment with 40 clusters/plant, and the lowest pH values and fresh mass of the bunches were observed for treatments with the highest and lowest levels of clusters thinning (15 and 60 clusters/plant). All attributes evaluated were greatly affected by the growing season. The practice of cluster thinning exhibited little beneficial effects on fruit quality of grapevines conducted in the horizontal overhead trellis under the climatic conditions of “Serra Gaúcha”.